A (des)ordem Imperial Brasileira: as lutas populares por cidadania no Maranhão no contexto de construção do Estado Nacional (1823-1841) - MATEUS, Yuri Givago Alhadef Sampaio (2023)
This dissertation aims to analyze the citizenship struggle in the construction context of the Brazilian imperial order, pointing out the active popular participation in this process, based on the struggles independence historical experience (1822-1823) and the september social movements (1831- 1832) and Balaiada (1838-1841) that took place in nineteenth- century Maranhão. The theoretical framework is based on the New Political History (Rémond, 2003) and Social History (Rudé, 1991), with emphasis on English Social History (Hobsbawm, 2010). This research problem is to understand how the popular segments reacted to the political exclusion process of the Brazilian imperial State and its exclusionary citizenship model. For this, the citizenship struggle is presented between political and social disputes in the political transition period in the Luso-Brazilian world and in the Post-Independence period, in which popular yearnings were manifested through protests and revolts in the face of these segments exclusion in the new political order that was being structured. The methodology used is based on bibliographical and documentary research (newspapers, letters, minutes, proclamations, etc.). The work guiding hypothesis is the popular struggles that took place in the construction context of the Brazilian imperial order, such as the Independence process movements the Setembrada and Balaiada, are constituents of disputes for socio-political participation and citizenship rights, foreseen in the Empire constitution from 1824, which implies that popular participation in this historical process had a broader reach and meaning than conservative interpretations suggest. In this view, it is questioned about the imperial order principles that (dis)orders of the people threatened so much. This research seeks to show the popular movements that took place in Maranhão in the 19th century (Fights for Independence, Setembrada and Balaiada), which had the free poor and enslaved people participation, presented claims that show the peculiar political reading of these popular layers, which involved their experience and the way in which they incorporated the new political ideas (liberalism, constitution, citizenship, among others) that circulated in that context.